The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/08039488.2014.994033
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Impulsive/Premeditated Aggression Scale in Mexican psychiatric patients

Abstract: The IPAS is an adequate instrument, which might be used to differentiate the type of aggressive behavior in Mexican psychiatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In the analysis of the explained variance described by other authors, we have observed that the IA factor can explain between 12.9% ( 41 ) and 24% ( 39 ) of the total IPAS variance; and that the PM factor can account for between 10.3% ( 42 ) and 15.6% ( 37 ) of the total IPAS variance. We have obtained higher values of explained variance (34.3% for the IA factor and 15.7% for the PM factor).…”
Section: Discussionmentioning
confidence: 54%
“…In the analysis of the explained variance described by other authors, we have observed that the IA factor can explain between 12.9% ( 41 ) and 24% ( 39 ) of the total IPAS variance; and that the PM factor can account for between 10.3% ( 42 ) and 15.6% ( 37 ) of the total IPAS variance. We have obtained higher values of explained variance (34.3% for the IA factor and 15.7% for the PM factor).…”
Section: Discussionmentioning
confidence: 54%
“…9,13,14 In order to assess these two types of aggression, Stanford et al 3 developed the Impulsive/Premeditated Aggression Scale (IPAS), which equally assesses the two aggressive patterns. The IPAS has been translated into Chinese, 15 Portuguese, 16,17 Spanish 18 and Dutch. 19 Research testing the factorial structure of the scale 4,[18][19][20] identified the expected main factors impulsive aggression (IA) and premeditated aggression (PM) and no significant differences in the distribution of the items across dimensions (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The IPAS has been translated into Chinese, 15 Portuguese, 16,17 Spanish 18 and Dutch. 19 Research testing the factorial structure of the scale 4,[18][19][20] identified the expected main factors impulsive aggression (IA) and premeditated aggression (PM) and no significant differences in the distribution of the items across dimensions (Table 1). Overall, in previous research, the scale demonstrated good psychometric properties across community, 20-22 forensic 4,23-25 and clinical samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations